(untitled) (Journal of the College of Education for Women, 2019)
In our previous research , we study the method of women by ( al – sakhaawi " died 902ah/1496a.c"book witch called ( al- dhau, al-lami) .So in this paper , we will discuss the social life of women in the mamluk period through thesame book ,especially when the sakhaawi devoted a full part for women in the same bookcalled it (mhagam ,al –nessa)wich it translations a large number of women like wives,daughters ,sisters ,and maids of mamluk sultans ,so that make my able to know a lot aboutthe social life of woman which we study it like a social aspects of women, here wealth,business, professions ,and in the last we study the habits of them marriage .